The Effect of Workload, Compensation, And Leadership Style On The Performance Of Matahari Sleman City Hall Employees - ulfa eka febriria nuriwati (ASIAN PUBLISHER, 2024)
The main determinant of the company's development path that is used as spearhead of progress is the performance of its human resources. The benefits of the research are to prove the influence of the three variables work results Matahari Sleman City Hall employees. The function of the research is to test the workload, compensation, and leadership style simultaneously whether it affects the performance of Matahari Sleman City Hall employees. The sampling amounted to 86 respondents and used a questionnaire as a test for validity and reliability. The results of classical assumption show that the regression model is normally distributed and no muliticallinearity occurs, and no heteroscedaticity occurs. So that Y = 1.146 + 0.356 X1 + 0.199 X2 + 0.218 X3 is . Finally, it can be seen that the performance of Matahari Sleman City Hall employees is influenced by workload, compensation, and leadership style because it is proven that all three have a significant effect on employee work results. Therefore, performance Matahari Sleman City Hall employees is simultaneously and significantly influenced by workload, compensation, and leadership style.